The role of Manalagi apple (Malus sylvestris Mill.) extract gel in fibronectin expression during traumatic ulcer healing - Achmad Gigih Andy Putra; Nikmatus Sa'adah; Andre Geromiko Himang; Herlambang Prehananto; Sawitri Dwi Indah Pertami; Endah Kusumastuti; Agus Aan Adriansyah; Siti Aisyah Abd Ghafar (Dentika: Dental Journal, 2026)
Traumatic ulcer is open wound caused by injury to the oral mucosa. Fibronectin, a multifunctional glycoprotein, has been reported to play a crucial role in early wound healing by promoting fibroblast migration. Several studies have shown that Manalagi apple (Malus sylvestris Mill.) contains bioactive compounds with anti-inflammatory, antioxidant, antibacterial, and wound healing properties. Therefore, this study aims to evaluate the effect of Manalagi apple extract gel on fibronectin expression in traumatic ulcer healing. This was a laboratory experimental study with a post-test only control group design. A total of 10 rats (Rattus norvegicus) were randomly divided into a placebo gel control group and a treatment group receiving 10% Manalagi apple extract gel. Fibronectin expression was then evaluated using immunohistochemical (IHC) staining, and analyzed with the Mann–Whitney test. The results showed a significant difference in fibronectin expression between the treatment and control groups (p = 0.007). The application of 10% Manalagi apple extract gel significantly increased fibronectin expression during traumatic ulcer healing.